Phosphorylation‐dependent osterix degradation negatively regulates osteoblast differentiation. Issue 11 (15th September 2020) - Hoshikawa, Seira; Shimizu, Kouhei; Watahiki, Asami; Chiba, Mitsuki; Saito, Kan; Wei, Wenyi; Fukumoto, Satoshi; Inuzuka, Hiroyuki
Abstract: Proteasome inhibitors exert an anabolic effect on bone formation with elevated levels of osteoblast markers. These findings suggest the important role of the proteasomal degradation of osteogenic regulators, while the underlying molecular mechanisms are not fully understood. Here, we report that the proteasome inhibitors bortezomib and ixazomib markedly increased protein levels of the osteoblastic key transcription factor osterix/Sp7 (Osx). Furthermore, we revealed that Osx was targeted by p38 and Fbw7 for proteasomal degradation. Mechanistically, p38‐mediated Osx phosphorylation at S73/77 facilitated Fbw7 interaction to trigger subsequent Osx ubiquitination. Consistent with these findings, p38 knockdown or pharmacological p38 inhibition resulted in Osx protein stabilization. Treatment with p38 inhibitors following osteogenic stimulation efficiently induced osteoblast differentiation through Osx stabilization. Conversely, pretreatment of p38 inhibitor followed by osteogenic challenge impaired osteoblastogenesis via suppressing Osx expression, suggesting that p38 exerts dual but opposite effects in the regulation of Osx level to fine‐tune its activity during osteoblast differentiation. Furthermore, Fbw7 ‐depleted human mesenchymal stem cells and primary mouse calvarial cells resulted in increased osteogenic capacity. Together, our findings unveil the molecular mechanisms underlying the Osx protein stability control and suggest that targeting the Osx degradation pathway could help enhance efficient osteogenesis and bone matrix regeneration.